The dip the extraordinary benefits of knowing when to quit and when to stick - Godin, Seth. (London Piatkus, 2007)
The old saying is wrong?winners do quit, and quitters do win.
Includes bibliographical references and index.
Keywords: Self-actualization (Psychology)